Metal matrix composite laser metal deposition for ballistic application - Adam, R; Botes, A; Corderley, G (IOP conference series. Materials Science and Engineering, 2018)
The armour development industry uses ceramic tiles to provide effective ballistic protection to critical areas of military vehicles. The ceramic tiles are generally attached to a ductile backing material by means of an adhesive, which often incorporates defects that are undesirable for ballistic protection. Laser cladding provides a more efficient approach for applying a ceramic material onto a ductile backing through metallurgically bonding the materials. A 3kW, IPG fiber laser system was used to manufacture test coupons to investigate the process parameters for the laser metal deposition of a tungsten carbide (chemical formula WC) metal matrix material onto an Armox 500 backing material. Results show that good fusion to the base material with limited solidification cracking can be achieved. Vickers microhardness and sound velocity results showed satisfactory results for a ballistic application.